Auricular Transcutaneous Vagus Nerve Stimulation Acutely Modulates Brain Connectivity in Mice - Brambilla-Pisoni, Cecilia; Muñoz-Moreno, Emma; Gallego-Amaro, Ianire; Maldonado, Rafael; Ivorra, Antoni; Soria, Guadalupe; Ozaita, Andrés (Frontiers in Cellular Neuroscience, 2022)
Brain electrical stimulation techniques take advantage of the intrinsic plasticity of the nervous system, opening a wide range of therapeutic applications. Vagus nerve stimulation (VNS) is an approved adjuvant for drug-resistant epilepsy and depression. Its non-invasive form, auricular transcutaneous VNS (atVNS), is under investigation for applications, including cognitive improvement. We aimed to study the effects of atVNS on brain connectivity, under conditions that improved memory persistence in CD-1 male mice. Acute atVNS in the cymba conchae of the left ear was performed using a standard stimulation protocol under light isoflurane anesthesia, immediately or 3 h after the training/familiarization phase of the novel object-recognition memory test (NORT). Another cohort of mice was used for bilateral c-Fos analysis after atVNS administration. Spearman correlation of c-Fos density between each pair of the thirty brain regions analyzed allowed obtaining the network of significant functional connections in stimulated and non-stimulated control brains. NORT performance was enhanced when atVNS was delivered just after, but not 3 h after, the familiarization phase of the task. No alterations in c-Fos density were associated to electrostimulation, but a significant effect of atVNS was observed on c-Fos-based functional connectivity. atVNS induced a clear reorganization of the network, increasing the inter-hemisphere connections and the connectivity of locus coeruleus. Our results provide new insights in the effects of atVNS on memory performance and brain connectivity extending our knowledge of the biological mechanisms of bioelectronics in medicine.